The impact of hegemonic masculine ideals on self‐esteem in prostate cancer patients undergoing androgen deprivation therapy (ADT) compared to ADT‐naïve patients. Issue 11 (10th August 2022) - Gentili, Caterina; McClean, Stuart; McGeagh, Lucy; Bahl, Amit; Persad, Raj; Harcourt, Diana
Abstract: Purpose: Androgen deprivation therapy (ADT) for Prostate Cancer (PCa) is associated with side effects that could lead to negative body image and low masculine self‐esteem of survivors. We compared a group of PCa survivors following ADT with ADT‐naïve patients, expecting the ADT group to show lower masculine self‐esteem. We also expected patients with hegemonic masculinity ideals to show poorer masculine self‐esteem and we hypothesized that ADT would moderate this relationship, expecting PCa patients on ADT with stronger hegemonic ideals to show the worst masculine self‐esteem scores among study participants. Methods: We compared 57 PCa survivors on ADT ( M age  = 64.16 (7.11)) to 59 ADT‐naïve patients ( M age  = 65.25 (5.50)), on the Masculine Self‐Esteem Scale (MSES), Body Image Scale (BIS), and Hegemonic Masculinity Ideals Scale (HMIS). Results: While the two groups did not significantly differ on masculine self‐esteem ( F  [1, 115] = 3.46, p  = 0.065, η p 2  = 0.029) and body image ( F [1, 115] = 3.46, p  = 0.065, η p 2  = 0.029), younger age was significantly associated with higher body image issues ( F [1, 115] = 8.63, p  < 0.01, η p 2  = 0.071, β  = −0.30). Hegemonic masculinity significantly predicted more masculine self‐esteem related issues ( t (2, 114) = 2.31, β  = 0.375, p  < 0.05). ADT did not moderate this relationship. Conclusions: The results suggest that endorsing hegemonic masculinity could represent a risk factor for low masculine self‐esteem regardless of ADT status and that younger age is associated with negative body image among PCa survivors. Implications: These results suggest the importance of inclusion of topics related to hegemonic masculinity when providing support to PCa survivors, both when discussing treatment side effects, as well as in the later phases of survivorship. This pilot also suggests that younger PCa survivors might benefit from body‐image focused support regardless of treatment plan.